Judicial Review and the Indian Constitution: Protecting Citizen Rights through Judicial Review in the Indian Constitution (Journal of Advances and Scholarly Researches in Allied Education, 2017)
To safeguard the rights of citizen of India, the judicial review is recognized as necessary and a basic requirement for construction up of a novel civilization, which is based on the perception of public. The power of judicial review is vested with the higher judiciary of states as well as with apex court. In India we follow the doctrine of separation of power as provided under article 50 of the constitution of India. And the principle of check and balance is also present in India, which is furthered by judicial review. Constitution is considered to be living document. There is n number of examples in which this has been used by our apex court to protect citizen from arbitrary action of executive, legislature etc.